Personnel development of schools in Phaeng sub-district administrative organization - วรพงศ์พัชร์ ณฐาพัชร์; Junsuk, Pornpawee (วิทยาการบริหารภาครัฐสมัยใหม่, 2024)
The objectives of this research were: (1) to study the personnel development of schools in Phaeng Subdistrict Administrative Organization under Kosum Phisai District in Maha Sarakham Province; and (2) to compare the personnel development of schools in Phaeng Subdistrict Administrative Organization under Kosum Phisai District in Maha Sarakham Province classified by age and work experience. This research methodology was survey research. The population consisted of 46 teachers at schools in Phaeng Subdistrict Administrative Organization under Kosum Phisai District in Maha Sarakham Province. The sample consisted of 42 teachers at schools in Phaeng Subdistrict Administrative Organization under Kosum Phisai District in Maha Sarakham Province, determined by Krejcie and Morgan’s table and obtained by a simple random sampling method. The instrument used for data collection was a five-point rating scale questionnaire. The statistics used in data analysis were frequency, percentage, mean, standard deviation, and t-test. The research findings found that: (1) the personnel development of schools in Phaeng Subdistrict Administrative Organization under Kosum Phisai District in Maha Sarakham Province was at a high level in overall aspects; and (2) the results of hypothesis testing showed that teachers with different ages and different work experiences had no different opinions toward the personnel development of schools in Phaeng Subdistrict Administrative Organization under Kosum Phisai District in Maha Sarakham Province.